Subliminal Advertising and its impact on Impulsive Buying Paradigms: An Empirical study of young consumers of India - Khawaja, Sarwar; Qureshi, Fayyaz Hussain; Sofi , Shakeel Ahmad (Journal of Ecohumanism, 2024)
The goal of this study is to examine the impact subliminal advertising on the impulsive buying behaviour among youth. Though the concept of subliminal advertising is gaining interest among scholars across the globe but there is still deficiency of literature in this domain. This research is a mix of both exploratory and descriptive designs which were employed to test the study in holistic manner. Both EFA and CFA were employed on 410 consumers and it has been found that subliminal advertising has strong influence on the impulsive buying predispositions and the application of Multi-group-Analysis employed for investigating the relationship between impulsive buying and advertisements while controlling gender and age differences has revealed that males are more susceptible than females and the consumers of younger age group are more vulnerable to subliminal exposure maneuvers.